To divide 2 1/6 by 1 1/3, we first need to convert the mixed numbers into improper fractions.
2 1/6 = (2 * 6 + 1) / 6 = 13 / 6
1 1/3 = (1 * 3 + 1) / 3 = 4 / 3
Now, we can divide the fractions:
(13 / 6) ÷ (4 / 3) = (13 / 6) * (3 / 4)
Multiplying the numerators and denominators, we get:
(13 * 3) / (6 * 4) = 39 / 24
Therefore, 2 1/6 divided by 1 1/3 is equal to 39 / 24.
2 1/6 divied 1 1/3
5 answers
wron g
I apologize for the mistake. Let's try again:
To divide 2 1/6 by 1 1/3, we need to find a common denominator for the fractions.
The common denominator of 6 and 3 is 6.
Next, we convert the mixed numbers into improper fractions:
2 1/6 = 13/6
1 1/3 = 4/3
Now, we divide the fractions:
(13/6) ÷ (4/3) = (13/6) * (3/4)
Multiplying the numerators and denominators, we get:
(13 * 3) / (6 * 4) = 39/24
But we can simplify this fraction by dividing the numerator and denominator by their greatest common divisor, which is 3:
39/24 = (39/3) / (24/3) = 13/8
Therefore, 2 1/6 divided by 1 1/3 is equal to 13/8.
To divide 2 1/6 by 1 1/3, we need to find a common denominator for the fractions.
The common denominator of 6 and 3 is 6.
Next, we convert the mixed numbers into improper fractions:
2 1/6 = 13/6
1 1/3 = 4/3
Now, we divide the fractions:
(13/6) ÷ (4/3) = (13/6) * (3/4)
Multiplying the numerators and denominators, we get:
(13 * 3) / (6 * 4) = 39/24
But we can simplify this fraction by dividing the numerator and denominator by their greatest common divisor, which is 3:
39/24 = (39/3) / (24/3) = 13/8
Therefore, 2 1/6 divided by 1 1/3 is equal to 13/8.
wrong
Apologies for the error. Let's correct it:
To divide 2 1/6 by 1 1/3, we need to convert the mixed numbers into improper fractions.
2 1/6 = (2 * 6 + 1) / 6 = 13 / 6
1 1/3 = (1 * 3 + 1) / 3 = 4 / 3
Now, we can divide the fractions:
(13 / 6) ÷ (4 / 3)
To divide fractions, we multiply the first fraction by the reciprocal of the second fraction:
(13/6) * (3/4)
We can simplify by canceling common factors:
(13 * 3) / (6 * 4) = 39 / 24
To further simplify, we can divide both the numerator and denominator by their greatest common divisor, which is 3:
39 / 24 = (39/3) / (24/3) = 13 / 8
Therefore, 2 1/6 divided by 1 1/3 is equal to 13/8.
To divide 2 1/6 by 1 1/3, we need to convert the mixed numbers into improper fractions.
2 1/6 = (2 * 6 + 1) / 6 = 13 / 6
1 1/3 = (1 * 3 + 1) / 3 = 4 / 3
Now, we can divide the fractions:
(13 / 6) ÷ (4 / 3)
To divide fractions, we multiply the first fraction by the reciprocal of the second fraction:
(13/6) * (3/4)
We can simplify by canceling common factors:
(13 * 3) / (6 * 4) = 39 / 24
To further simplify, we can divide both the numerator and denominator by their greatest common divisor, which is 3:
39 / 24 = (39/3) / (24/3) = 13 / 8
Therefore, 2 1/6 divided by 1 1/3 is equal to 13/8.